Recreation of the Edinburgh potato Solanum × edinense Berthault: A historically and economically important potato hybrid - Sánchez-Ganfornina, Diego; Tapson, Jan; Sutherland, Liz; Coleman, Max (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2020)
Solanum × edinense Berthault is a spontaneously occurring hybrid between S. demissum Lindl. and the cultivated potato, S. tuberosum L., found near potato fields in Mexico. Although not described until 1911, this hybrid was in cultivation at the Royal Botanic Garden Edinburgh (RBGE) shortly after the Irish Potato Famine of 1845–1849 and proved to be highly resistant to late blight, Phytophthora infestans. In the mid-19th century late blight caused widespread failure of the potato crop across Europe and played a central role in the Irish Potato Famine. Using the parent species in controlled crosses we have recreated the hybrid that was named by Berthault in recognition of RBGE as the source of his plant material. We have also researched the early history of this hybrid potato in Edinburgh and demonstrated disease resistance through field exposure during the outbreak of late blight in Edinburgh in 2019. This work underlines the important role of this hybrid in the breeding of disease-resistant potato cultivars.